2021
DOI: 10.1038/s41539-021-00092-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations between school enjoyment at age 6 and later educational achievement: evidence from a UK cohort study

Abstract: Education is influenced by a broad range of factors but there has been limited research into the role that early school enjoyment plays in pupil’s educational achievement. Here we used data from a UK cohort to answer three research questions. What is the association between early school enjoyment and later academic achievement? To what extent do family background factors underlie this association? Do sex differences in school enjoyment underlie sex differences in achievement? School enjoyment was self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
0
20
0
2
Order By: Relevance
“…Fluency of English or English as an additional language showed inconsistent results with one high quality study showing no association (Fletcher et al, 2015) and another showing that students with English as an additional language at ages 6-12 years were more likely to have better KS4 attainment (Gorard and Siddiqui, 2019). Both age and quality of friendships also showed inconsistent results with some studies showing no association (age: Sammons, 1995;Sammons et al, 1995; quality of friendships: Morris et al, 2021) and others suggesting that younger students (Gorard and Siddiqui, 2019) and students with peer problems were more likely to have lower attainment at GCSE/KS4. There was insufficient evidence for physical activity, special educational needs and disabilities status, bullied status, autistic traits, confidence, entry into care, school enjoyment, whether student likes their teacher, and motivation to write in middle childhood.…”
Section: Student Factorsmentioning
confidence: 99%
“…Fluency of English or English as an additional language showed inconsistent results with one high quality study showing no association (Fletcher et al, 2015) and another showing that students with English as an additional language at ages 6-12 years were more likely to have better KS4 attainment (Gorard and Siddiqui, 2019). Both age and quality of friendships also showed inconsistent results with some studies showing no association (age: Sammons, 1995;Sammons et al, 1995; quality of friendships: Morris et al, 2021) and others suggesting that younger students (Gorard and Siddiqui, 2019) and students with peer problems were more likely to have lower attainment at GCSE/KS4. There was insufficient evidence for physical activity, special educational needs and disabilities status, bullied status, autistic traits, confidence, entry into care, school enjoyment, whether student likes their teacher, and motivation to write in middle childhood.…”
Section: Student Factorsmentioning
confidence: 99%
“…Research indicates that students' learning-related beliefs and feelings develop early and are important for academic performance (Stipek & Ryan, 1997). For example, school enjoyment at age 6 is associated with cross-discipline achievement 10 years later (Morris et al, 2021). School enjoyment is related to the affective components of curiosity, including "liking" or "enjoying" trying new things, which are associated with school readiness and learning (Lamnina & Chase, 2019;Litman, 2008;Shah et al, 2018), perhaps through promoting curiosity and higher engagement in more meaningful learning experiences, such as using constructive cognitive practices like making connections to material (both personal connections and across topics) or identifying gaps in one's knowledge and asking related questions (Chi & Wylie, 2014;Jirout, 2020;Jirout et al, 2018).…”
Section: Relation Between School Readiness and School Enjoymentmentioning
confidence: 99%
“…In a recent study using a three-item scale to measure preschool children's school enjoyment (Lichtenfeld et al, 2012;Ruzek et al, 2020), school enjoyment related to other important motivational factors and learning orientations, including growth mindset, perceived academic competence, peer social skills, and task orientation (Ruzek et al, 2020). These associations provide potential explanations for the observed link between school enjoyment and achievement (e.g., Morris et al, 2021), discussed further below. Importantly, enjoyment is associated with academic achievement across populations (Ainley & Ainley, 2011), with a universal relation observed in all 68 PISA participating countries (Loderer et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there is a substantial body of international research that highlights benefits to children and societies of reading for pleasure and shows that children's reading is sustained within a complex of psychological, social, and material relations in which fostering and sustaining interest and engagement through enjoyment is key (Burnett & Merchant, 2018;Cremin et al, 2014;Gutiérrez, 2008). There is also considerable evidence that enjoyment enhances learning, including a study of children in England that showed enjoyment of school at age 6 predicted substantially higher attainment 10 years later (Morris et al, 2021). Many factors that influence educational achievement, such as socioeconomic factors, are outside the sphere of schools.…”
Section: Introductionmentioning
confidence: 99%